2006
DOI: 10.1007/s00384-005-0077-2
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative urinary retention after surgery for benign anorectal disease: potential risk factors and strategy for prevention

Abstract: Urinary retention is a common complication after anorectal surgery. It is linked to several risk factors, including increased intravenous fluids and postoperative pain. Perioperative fluid restriction and adequate pain relief appear to be effective in preventing urinary retention in a significant number of patients after anorectal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
3
21

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(155 citation statements)
references
References 16 publications
7
124
3
21
Order By: Relevance
“…LUTS, the only subjective factor in the meta-analysis, was defined by only one study 40 and retrospectively applied in four of the six. Despite none of these studies being considered of low methodological quality on NOS assessment, the authors considered these papers at high risk of selection and reporting biases.…”
Section: Methodological Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…LUTS, the only subjective factor in the meta-analysis, was defined by only one study 40 and retrospectively applied in four of the six. Despite none of these studies being considered of low methodological quality on NOS assessment, the authors considered these papers at high risk of selection and reporting biases.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…The only two studies that demonstrated a significant relationship both identified male gender as protective 40,45 , however once the studies had been pooled, male sex was not found to significantly influence the risk of developing POUR with a summary OR of 0.96 (figure 2, 95% CI 0.62-1.50, p=0.87). Including only prospective studies did not affect the lack of association between sex and POUR (data not shown).…”
Section: Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…3,11,14,15,17,18,83 Urinary retention is dependent on the severity of disease and degree of surgery, the analgesia requirement and pre-existing bladder outlet compromise. [85][86][87] In addition, day case treatment may reduce the incidence. 88 Both cases of urinary retention in our trial had HAL combined with significant mucopexy (more than five mucopexy sutures).…”
Section: Surgical Complicationsmentioning
confidence: 99%
“…Post-operative urinary retention (POUR) is defined as the inability to void after surgery when the bladder is full (1,2) POUR is common and represents between 5% to 70% of all surgeries (1), especially after herniorrhaphy (3,4) and anorectal surgery (5)(6)(7). Typically, this phenomenon is painful and can result in increased cost of hospitalization, prolonged length of hospital stay, bladder overdistension, and urinary tract infection (UTI) which can occur primarily or secondarily to catheterization (1,8).…”
Section: Introductionmentioning
confidence: 99%